Innovation and tourism: Between territorial reproduction and sustainable development - Lamya Maghnaoui (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: Located less than an hour from the red city of Marrakech, the Ourika valley is experiencing rapid (environmental, demographic, sociocultural, economic, etc.,) changes. The local way of life and conventional production methods are also being shaken up by these developments. This study’s central focus will guide this introspection and embed it within the larger framework of a territory project designed to organize these areas’ underlying resources and physical territory (what can be done; what happens there; offers channels; events). Different types of wellness tourism can be viewed as part of a sustainable, cross-border innovation and appreciation for, valorization, combination, and connection. Methodology: Since this research required an objective examination of preexisting phenomena and eve nts that could not be influenced by the researcher, we opted for a quantitative approach. The data can be analyzed by exploring the information and extrapolating the findings to the entire population. Findings: It is important to take advantage of the opportunity presented by the tourist gardens because the product can help to diversify the valley’s tourism industry. Also, the Ourika valley is off-limits for displaying or discussing aromatic and medicinal plants. This sector is indeed highly respected, professionally run, and widely recognized. Several national and international brands have recognized the quality and value of these plants in cosmetics, care, and well-being, so they are supplied to those businesses. Implications/Novel Contribution: This research delves deeper into the Moroccan tourism industry and the novel factors that boost tourism-related pursuits in the country. Other similar settings may get many policy take aways from this current research.